2008
DOI: 10.29173/istl2440
|View full text |Cite
|
Sign up to set email alerts
|

Library Research Skills: A Needs Assessment for Graduate Student Workshops.

Abstract: Information literacy instruction programs for graduate students can be challenging to develop. One solution is to develop non-course-based, non-mandatory library instruction programs, in order to meet the information literacy needs of as many graduate students as possible. This was the approach taken by the Taylor Library at the University of Western Ontario, as we embarked on the development of a program for students in the areas of engineering, health sciences, medicine & dentistry, and science. As a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There is a substantial amount of library literature demonstrating that graduate students need workshops offered by academic libraries, and this need is not novel (Bussell et al, 2017;Critz et al, 2012;Hoffmann et al, 2008;O'Malley and Delwiche, 2012;Peacemaker and Roseberry, 2017;Rempel, 2010;Roszkowski and Reynolds, 2013;Saetnan, 2020). While graduate and postgraduate students need library workshops, academic libraries struggle with workshop attendance (Alvarez et al, 2014;Bussell et al, 2017;Critz et al, 2012;Fong et al, 2016;O'Malley and Delwiche, 2012;Peacemaker and Roseberry, 2017;Saetnan, 2020;Witherspoon and Taber, 2021).…”
Section: Graduate Student Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a substantial amount of library literature demonstrating that graduate students need workshops offered by academic libraries, and this need is not novel (Bussell et al, 2017;Critz et al, 2012;Hoffmann et al, 2008;O'Malley and Delwiche, 2012;Peacemaker and Roseberry, 2017;Rempel, 2010;Roszkowski and Reynolds, 2013;Saetnan, 2020). While graduate and postgraduate students need library workshops, academic libraries struggle with workshop attendance (Alvarez et al, 2014;Bussell et al, 2017;Critz et al, 2012;Fong et al, 2016;O'Malley and Delwiche, 2012;Peacemaker and Roseberry, 2017;Saetnan, 2020;Witherspoon and Taber, 2021).…”
Section: Graduate Student Populationmentioning
confidence: 99%
“…, 2017; Critz et al. , 2012; Hoffmann et al. , 2008; O'Malley and Delwiche, 2012; Peacemaker and Roseberry, 2017; Rempel, 2010; Roszkowski and Reynolds, 2013; Saetnan, 2020).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…• This effect has been widely studied [1][2][3]7]. • "In Press" references must include the name of the journal.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Of the research that has been done on graduate-level IL, much of it relates to information behavior and needs, rather than instruction or assessment [6]. Several studies were found that assessed the efficacy of outreach and instruction strategies specifically for graduate students, such as workshops targeted to specific needs [7], express classes [8], and embedded consultation models [9], [10]. Citation analyses of upper-level and graduate-level literature reviews, theses, and dissertations show that as students progress up the curriculum, they tend to cite increasingly more sources, and more scholarly sources [11], [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Universities have deployed various means to select and assess graduate workshops. Hoffman et al utilized information from surveys and focus groups to plan their series [9]. Peacemaker and Roseberry relied on a combination of their experiences as librarians in course-integrated instruction, gaps in their own knowledge, and graduate student feedback to select topics [10].…”
Section: Literature Reviewmentioning
confidence: 99%